2014
DOI: 10.1175/jcli-d-13-00331.1
|View full text |Cite
|
Sign up to set email alerts
|

An Updated TRMM Composite Climatology of Tropical Rainfall and Its Validation

Abstract: An updated 15-yr Tropical Rainfall Measuring Mission (TRMM) composite climatology (TCC) is presented and evaluated. This climatology is based on a combination of individual rainfall estimates made with data from the primary TRMM instruments: the TRMM Microwave Imager (TMI) and the precipitation radar (PR). This combination climatology of passive microwave retrievals, radar-based retrievals, and an algorithm using both instruments simultaneously provides a consensus TRMM-based estimate of mean precipitation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 54 publications
(33 citation statements)
references
References 22 publications
3
30
0
Order By: Relevance
“…The GPCP ocean magnitudes also compare well (within a few percent) with TRMM climatology estimates in the tropics (Adler et al 2009;Wang et al 2014). In addition, recent studies using TRMM plus CloudSat information by Behrangi et al (2012Behrangi et al ( , 2014 report ocean precipitation that is 4.3% above GPCP, and Trenberth et al (2009) applied a 5% increase to GPCP ocean precipitation in their analysis.…”
Section: B Evaluation Of Metricssupporting
confidence: 57%
“…The GPCP ocean magnitudes also compare well (within a few percent) with TRMM climatology estimates in the tropics (Adler et al 2009;Wang et al 2014). In addition, recent studies using TRMM plus CloudSat information by Behrangi et al (2012Behrangi et al ( , 2014 report ocean precipitation that is 4.3% above GPCP, and Trenberth et al (2009) applied a 5% increase to GPCP ocean precipitation in their analysis.…”
Section: B Evaluation Of Metricssupporting
confidence: 57%
“…The TRMM program has three different algorithm products: one based on the passive microwave instrument, the TMI; one based on the radar, the PR; and one based on a combination of the two instruments. The three estimates have been combined into a TRMM composite climatology (TCC) Wang et al 2014), where the local spread among the estimates provides a measure of confidence in the result. As indicated by the spread of estimates in some locations (and the maps in the referenced articles), there can be significant differences between these three estimates in certain regions, but over the large area of the tropical oceans, they are within a few percent of each other, as seen in Table 2.…”
Section: Global and Tropical Mean Precipitationmentioning
confidence: 99%
“…from the GPCP (Global Precipi-overestimation of 8 to 10 %. Note that these comparisons were done against measurements on atolls, although the representativeness of the atoll gauges of open-ocean rainfall is still an unanswered question (Wang et al, 2014). Andersson et al (2011) have shown that HOAPS gives lower precipitation rates than ERA-Interim, except for small areas in the northern subtropics, the north-western and south-western Atlantic Ocean.…”
Section: Introductionmentioning
confidence: 99%